Investment of banks to facilitate and benefit the small and medium as well as minor entrepreneur: First Security Islami Bank Ltd., Biswa Road Branch - Hasan, Kamrul (BRAC University, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.